Struktur dan Kaidah Kebahasaan Kumpulan Cerita Fabel dalam Buku Teks Bahasa Indonesia Kelas VII - Helmi, Tia Delpira (UIR PRESS, 2022)
Fable stories are animal stories intended to personify human characters. The animals that are used as story characters can talk, behave, and behave like humans. This research is entitled